Probing the shear and layer breathing modes in multilayer graphene by Raman spectroscopy. (13th November 2017) - Lin, Miao‐Ling; Wu, Jiang‐Bin; Liu, Xue‐Lu; Tan, Ping‐Heng
Abstract : The measurements of interlayer vibrations in multilayer graphene (MLG) have triggered a huge effort to understand phonons, electron–electron, electron–phonon, magneto–phonon interactions and the effect of layer number, stacking sequences, and layer orientations on the Raman spectroscopy of MLG. Here, we provide a review on the optical probe of interlayer vibrations, comprising the shear (C) and layer breathing (LB) modes. At first, we discuss different symmetries of MLGs in AB, ABC, and twisted stacking with an example of trilayer graphene, which dramatically influence the observations of interlayer vibrations. Then a brief description about the physical origins of the C and LB modes is introduced. Finally, two ways are elucidated to probe the interlayer modes in detail. The C and LB modes can be directly probed in the ultralow‐wavenumber Raman spectroscopy with special configurations, as depicted by the Raman spectra in MLG with diverse stacking orders. On the other hand, the LB modes can also be derived from the two‐phonon overtones in doubly resonant Raman spectra. These approaches can be extended to the other two‐dimensional layered materials, which pave the way to measure the interlayer coupling from experiments and thus greatly benefit the future research studies on their fundamental physics and potential applications. Copyright © 2017 JohnWiley & Sons, Ltd. Abstract : A review on the Raman probe of interlayer vibrations, comprising shear (C) and layer breathing (LB) modes, has been provided. The symmetries of multilayer graphene (MLG) in AB, ABC, and twisted stackingwere introduced firstly, and then the detailed physical origins of the C and LB modes are also addressed. Finally, two ways are elucidated to probe the interlayer modes. The fundamental C and LB modes can be directly probed via the ultralow‐wavenumber Raman spectroscopy.